Analisis Persaingan Pasar Air Minum Galon Pada Brand Aqua Dan Le Minerale - Shinta Damayanti; Siti Salma Nur Izati; Syamsul Hidayat (Journal of Management and Social Sciences, 2024)
The gallon drinking water market in Indonesia is one of the most competitive markets. This is due to several factors, including the high public demand for drinking water liters and the large number of competing brands. Ultimately, choosing the best brand of bottled water will be a decision based on individual needs. The purpose of this study is to help people make better decisions in choosing the appropriate gallon bottled water for consumption. The population in this research is consumers of gallon drinking water on the Aqua and Le Minerale brands in the Bina Bangsa Campus environment, especially regular management students 4 semester 5, with a sample size of 300 people. The results of hypothesis testing show Competition in the Gallon Drinking Water Market in the Aqua and Le Minerale Brands. We recommend that gallon mineral water in the Aqua and Le Minerale brands maintain quality by maintaining water purity.